The security forces and the police in the Colombian post-conflict (2014)
This paper raises an hypothesis about the role of the security forces in post-conflict, because instead of engaging in war, public policies should be implemented to articulate them around tasks of peace, such as infrastructure construction where military engineers could play a good role. The investment for the war, which is a sterile expenditure-, must be reoriented towards peace through strategies of presence with works of the State throughout the country. The issue becomes more effective on the occasion of the release of General Alzate and the resumption of the Havana Talks, looking at the extreme povertyof Chocó Department.